2020
DOI: 10.3390/ijerph17124605
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Related Quality of Life in Post-Laryngectomy Rehabilitation: Tracheoesophageal Fistula’s Wellness

Abstract: (1) Introduction: Laryngeal cancer is one of the most common types of cancer affecting the upper aerodigestive tract. Despite ensuring good oncological outcome in many locoregionally advanced cases, total laryngectomy is associated with relevant physical and psychological sequelae. Treatment through tracheo-esophageal speech, if promising, can lead to very variable outcomes. Not all laryngectomee patients with vocal prosthesis benefit from the same level of rehabilitation mainly due to the development of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…This study demonstrated equivalent 2-year overall survival (OS) in patients with advanced-stage larynx cancer randomized to induction chemotherapy with definitive radiation therapy (CRT) vs surgery. Treatment with CRT for laryngeal preservation was not associated with functional morbidity and quality-of-life limitations associated with surgery, suggesting that nonsurgical therapy may be an equivalent standard of care for advanced laryngeal cancer . With a local recurrence rate of 36% after primary definitive CRT, salvage TL with intent to cure was necessary for persistent or recurrent disease …”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated equivalent 2-year overall survival (OS) in patients with advanced-stage larynx cancer randomized to induction chemotherapy with definitive radiation therapy (CRT) vs surgery. Treatment with CRT for laryngeal preservation was not associated with functional morbidity and quality-of-life limitations associated with surgery, suggesting that nonsurgical therapy may be an equivalent standard of care for advanced laryngeal cancer . With a local recurrence rate of 36% after primary definitive CRT, salvage TL with intent to cure was necessary for persistent or recurrent disease …”
Section: Introductionmentioning
confidence: 99%
“…A further assessment by Agarwal et al found long-term outcomes of the V-RQoL reported higher patient satisfaction with the crucial contribution of social support (about 80% V-RQoL excellent score and >75% minimal VHI score). The quality-of-life questionnaire discovered significantly better outcomes in both socio-emotional and functional domains in the tracheoesophageal patient group compared to the esophageal group (p = 0.01; p = 0.01, respectively) in post-laryngectomy rehabilitation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, most healthcare services considered not urgent or elective (such as the SLP clinics) have experienced a considerable interruption or fragmentation of their activities [18]. Therefore, the COVID-19 pandemic has obliged the healthcare system to significantly transform its service offer and delivery modality, thus promoting a rapid expansion of the telehealth and TRH [19][20][21].…”
Section: Introductionmentioning
confidence: 99%